The Effect of Service Quality on Grab Bike Customer Satisfaction in Lagoa Village, North Jakarta - Sonia, Fara; Irawan, Pristanto Ria; Army, Widya Lelisa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Increasingly digital era develop fast , service transportation based application has become an integral part of life daily urban society . Grab Bike , as one provider the leading online motorcycle taxi service in Indonesia, has give contribution significant in make it easier mobility public . along with increasing user service this , quality service become factor decisive key satisfaction customer . Quality service in context Grab Bike services include various aspect , start from speed and accuracy time , attitude and behavior driver , convenience use application , up to safety and comfort during journey . All aspect This role important in form perception customer to services received and , ultimately , influence level satisfaction they . For That writer interested write study with quality variables service and satisfaction customer . The aim of this research is to determine the partial influence of service quality on Grab Bike customer satisfaction in Lagoa Village, North Jakarta. This research uses a quantitative descriptive method with data collection techniques through distributing questionnaires and library data. In this research, a purposive sampling method was used, totaling 45 Grab Bike users in the Lagoa sub-district, North Jakarta, using a simple linear regression data analysis technique. The results of this research show that there is a partial influence of service quality on Grab Bike customer satisfaction in Lagoa Village, North Jakarta. It is hoped that the results of this research will contribute to further research